2012
DOI: 10.1177/1368430212467476
|View full text |Cite
|
Sign up to set email alerts
|

Believing in “making a difference” to collective efforts: Participative efficacy beliefs as a unique predictor of collective action

Abstract: When rational actors believe that their group can achieve its goals through collective action (i.e., when they have strong group efficacy beliefs), they should not participate in it because they expect little benefit from their own participation. Paradoxically, however, research shows that individuals are more likely to participate when their group efficacy beliefs are stronger. In contrast to approaches that explain this paradox by invoking different psychological mechanisms (e.g., group identity, groupbased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
168
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(187 citation statements)
references
References 23 publications
(68 reference statements)
13
168
1
5
Order By: Relevance
“…Our study suggests that participative efficacy -the belief that one's individual contribution to the collective cause will make a difference (van Zomeren et al, 2013) -is unachievable if (some of) the group's actions are seen as illegitimate. People may weigh up the fit between their convictions, the perceived legitimacy of the physical groups who represent their social identity (i.e., their psychological group membership), the legitimacy and efficacy of the action-norms (or methods) of those groups, and how this effects their participative efficacy.…”
Section: Perceptions Of Protesters and Collective Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study suggests that participative efficacy -the belief that one's individual contribution to the collective cause will make a difference (van Zomeren et al, 2013) -is unachievable if (some of) the group's actions are seen as illegitimate. People may weigh up the fit between their convictions, the perceived legitimacy of the physical groups who represent their social identity (i.e., their psychological group membership), the legitimacy and efficacy of the action-norms (or methods) of those groups, and how this effects their participative efficacy.…”
Section: Perceptions Of Protesters and Collective Actionmentioning
confidence: 99%
“…Yet, research also shows that people evaluate the efficacy of collective action in contextually adaptive, and often seemingly paradoxical ways (Hornsey et al, 2006;van Zomeren, Leach, & Spears, 2010). Of particular interest in this study is the link between individual and group efficacy known as 'participative efficacy' -that is, individuals' belief that they can make an incremental contribution to the group (van Zomeren, Saguy, & Schellhaas, 2013).…”
Section: Social Identity Non-integration Social Disincentives and Imentioning
confidence: 99%
“…The vacant lot scenario may still come through under collective-level motivation, external or internal (see Table 1). However, as discussed in the literature review, these constructs are fragile and depend on social identity and on participants' belief that the outcome is achievable and is determined by their contribution (Van Zomeren et al, 2013). Moreover, as discussed in the literature review, the root of social identity lies in separation by inter-group distinctiveness, forestalling cooperation beyond the scope of the close group, thus thwarting the wider cooperation required to address many social and environmental dilemmas.…”
Section: Discussionmentioning
confidence: 99%
“…Van Zomeren, Saguy, and Schellhaas (2013) tried to reconcile the paradox of collective action, attempting to explain why people do cooperate, whereas according to Olson's free rider theory they should just enjoy the benefit without incurring to costs of cooperation, formulating the concept of participative efficacy, which is the belief that one's own actions will "make a difference" to collective efforts at achieving group goals. Preliminary evidence suggested that this factor is an independent and significant predictor of participation intention in collective action (Van Zomeren et al, 2013). Another attempt to bridge this gap with Olson's free rider theory was made by economists Akerlof and Kranton (2005), who suggested that the utility function includes social identity, where the motivation for collective action springs from an inner obligation (i.e., internal motivation) engendered by the acceptance of group norms via social identity.…”
Section: Collective Actionmentioning
confidence: 99%
See 1 more Smart Citation